2015
DOI: 10.1248/bpb.b15-00217
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Inhibition of hOAT1 and hOAT3 by Anthraquinones

Abstract: We previously showed that anthraquinones (including rhein, emodin, aloe-emodin, chrysophanol and physcion) were inhibitors of human organic anion transporter 1 (hOAT1) and hOAT3, causing transporter-mediated drug-drug interactions in rats. In this study, the time-dependent inhibition (TDI) of hOAT1 and hOAT3 by anthraquinones was investigated. Madin-Darby canine kidney (MDCK)-hOAT1, HEK293-hOAT3 and their parental cells were used. Preincubation with chrysophanol or physcion for 30 min significantly increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…In addition, there were toxic metabolites by naphthalene and anthraquinone bioactivation pathways . Chrysophanol exhibited significant time‐dependent inhibition for human organic anion transporter 1 (hOAT1), hOAT3 and hOAT4 in 0–60 min …”
Section: Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there were toxic metabolites by naphthalene and anthraquinone bioactivation pathways . Chrysophanol exhibited significant time‐dependent inhibition for human organic anion transporter 1 (hOAT1), hOAT3 and hOAT4 in 0–60 min …”
Section: Pharmacologymentioning
confidence: 99%
“…[80] Chrysophanol exhibited significant time-dependent inhibition for human organic anion transporter 1 (hOAT1), hOAT3 and hOAT4 in 0-60 min. [81] Pharmacokinetics Researcher found that the accumulation of chrysophanol in Caco-2 cells was four times higher than emodin, which may be related to the structure of chrysophanol and emodin and the specific transport system. [82] The main metabolic pathway of the bound anthraquinones was the hydrolysis of the glycosidic group followed by hydrogenation of the quinone moiety or further acetylation.…”
Section: Toxicitymentioning
confidence: 99%
“…Early evidence for this came from studies in which the inhibitory effect of a single dose of CsA on the hepatic clearance of bromsulphthalein persisted for at least 3 days in rats (Shitara et al, 2009), and preincubation before coincubation of OATP1B1 with CsA, compared with coincubation only, resulted in up to a 20-fold reduction in the measured IC 50 values (Amundsen et al, 2010;Shitara et al, 2012). Recent literature indicates that additional compounds, including ritonavir, saquinavir, and anthraquinones, can exert a more potent inhibition of uptake transport activity upon preincubation (Amundsen et al, 2010;Shitara et al, 2013;Ma et al, 2015;Shitara and Sugiyama, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies concerning PTIP have focused on OATPs, prompting regulatory agencies to recommend the inclusion of a preincubation step when OATP transport inhibition is being examined. Although sporadic studies have addressed the effect of preincubation on OATs (Ma et al, 2015) and OCTs (Arakawa et al, 2017), the lack of a systematic examination of non-OATP transporters has limited our knowledge of whether such mechanisms may be of additional clinical relevance.…”
Section: Introductionmentioning
confidence: 99%
“…While the plasma concentrations of the inhibitor drug are used for DDI prediction, the actual concentrations of inhibitor that the transporter encounters at the site of inhibition may be significantly different and difficult to measure. Lastly, substrate-dependent and time-dependent inhibitions have been recently reported 136 , 137 , 138 , 139 , which further complicates the assessment and in vitro –to– in vivo prediction of DDIs. Nevertheless, the field of drug transporters is rapidly evolving.…”
Section: Discussionmentioning
confidence: 99%